Impact of the COVID-19 Pandemic on Orthopaedic and Trauma Surgery in University Hospitals in Germany: Results of a Nationwide Survey. (15th July 2020) - Haffer, Henryk; Schömig, Friederike; Rickert, Markus; Randau, Thomas; Raschke, Michael; Wirtz, Dieter; Pumberger, Matthias; Perka, Carsten
Abstract : Background: The purpose of the present study was to assess the impact of the coronavirus disease 2019 (COVID-19) pandemic on orthopaedic and trauma surgery departments in university hospitals in Germany in order to clarify current challenges. Methods: In this cross-sectional study, an online-based anonymous survey was conducted within the Convention of University Professors of Orthopaedic and Trauma Surgery in Germany from April 3 to April 11, 2020. A bipolar 5-point Likert scale (with possible responses of "totally disagree, " "rather disagree, " "neutral, " "rather agree, " and "totally agree") was applied. Fifty-two (69.3%) of 75 clinic directors participated. Results: Communication and cooperation with the government, hospital administration, and other departments during the COVID-19 pandemic were mainly perceived as appropriate. However, only 7 respondents (13.7%) totally agreed or rather agreed with the statement that the authorities are supporters of orthopaedic and trauma surgery departments. Substantial financial and personnel changes in orthopaedic and trauma surgery departments of university hospitals were reported, resulting in an average reduction of 49.4% in operating room capacity and an expected 29.3% loss of revenue. In addition, 14.7% of physicians were reallocated from orthopaedic and trauma surgery to other care-delivery environments. Conclusions: Our study demonstrated that the COVID-19 pandemic has had a substantial impact on orthopaedic and trauma surgery departments in German university hospitals. Distinct structural and financial effects were noted. Nevertheless, the present study demonstrates the commitment of our specialty to overcome the pandemic by providing competent personnel as well as close cooperation with the hospital administration and other departments. Clinical Relevance: To our knowledge, this is the first Germany-wide survey among the heads of orthopaedic and trauma surgery departments in university hospitals on the impact of the COVID-19 pandemic. The survey results may help to inform system-wide decision-making in Germany, in Europe, and beyond.